Design and Fabrication of Garbage Collector on the Beach Using Solar Power - A, Arun.; P, Nagasankar; P, Amirthalingam; kumar. .E, Barath; G, Janarthanan.; AS, Magesh (International Journal of Engineering and Technology, 2018)
Beach sand cleaning is one of the most needed aspects that have to be implemented for clean future.   Even though many organizations are involved in removing the debris the amount of debris keeps on increasing day by day. From the various studies related to this paper, we found that a general awareness is created for the public regarding the environmental pollution and also machines are created with a complication in design and lack of efficiency. So, we have come up with a machine which is capable of collecting the garbage’s from the beach and that too with the simple design. Here the beach sand is cleaned by some mechanical equipment like conveyor, motor, gears which gives a fine outcome of the result. The Solar power is the main source of energy used in this machine. A 50 Watts monocrystalline solar panel is used for better results. The power from panel stores in a 24-volt 14 amps Lithium-Ion battery which then moves on to the motor which runs the conveyor and the machine.
Keywords: Garbage collector; solar power; hybrid garbage collector; beach garbage collector